Reduction of the infectivity of Toxoplasma gondii and Eimeria stiedai sporozoites by treatment with bovine lactoferricin - Omata, Y. (Obihiro Univ. of Agriculture and Veterinary Medicine, Hokkaido (Japan)); Satake, M; Maeda, R; Saito, A; Shimazaki, K; Yamauchi, K; Uzuka, Y; Tanabe, S; Sarashina, T; Mikami, T (Journal of Veterinary Medical Science, 2001)
Sporozoites of Toxoplasma gondii preincubated with lactoferricin showed decreased activity in penetration of mouse embryonal cells. Mice inoculated with 105 sporozoites preincubated with lactoferricin showed a higher survival rate than those inoculated with the same number of untreated sporozoites. Likewise, sporozoites of Eimeria stiedai preincubated with lactoferricin also showed decreased activity in penetration of rabbit hepatobiliary cells. Rabbits inoculated with 105 sporozoites preincubated with lactoferricin shed fewer oocysts than those inoculated with the same number of untreated sporozoites. These results indicate that lactoferricin is effective to reduce the infectivity of sporozoites of Toxoplasma gondii and Eimeria stiedai.